Constructing water-resistant CH3NH3PbI3 perovskite films via coordination interaction. Issue 43 (19th October 2016) - Li, Bo; Fei, Chengbin; Zheng, Kaibo; Qu, Xuanhui; Pullerits, Tönu; Cao, Guozhong; Tian, Jianjun
Abstract : 2-aminoethanethiol in perovskite films improves the intrinsic water-resistance, and the films can retain the MAPbI3 perovskite crystal structure when immersed in water for a long time (>10 minutes). Abstract : Organic–inorganic halide CH3 NH3 PbI3 (MAPbI3 ) perovskite solar cells (PSCs) have attracted intensive attention due to their high power conversion efficiency and low fabrication cost. However, MAPbI3 is known to be very sensitive to humidity, and the intrinsic long-term stability of the MAPbI3 film remains a critical challenge. 2-Aminoethanethiol (2-AET) was used as a ligand to bridge the organic compound (MAI) and inorganic compound (PbI2 ), which restricted the fast growth of PbI2 to realize the synchronous growth environment of MAI and PbI2 crystals, resulting in the formation of a compact MAPbI3 film with polygonal grains. Due to the compact (PbI2 )–2-AET–(MAI) molecule barrier layers in the MAPbI3 structure, the resulting perovskite films showed excellent intrinsic water-resistance, with the MAPbI3 perovskite crystal structure retained for a long time (>10 minutes) after immersion in water. This work makes a step towards obtaining long-term stable MAPbI3 perovskite devices.